Analyze The Factors of Organizational Citizenship Behavior on Starbucks’ Manager in Surabaya - Hellen Windiawatty Andahara Basary (Jurnal Ekonomi, 2020)
The objective of this study is to examine the influence of factors on OCB on Starbucks' Managers in Surabaya. The population is the managers of Starbucks Surabaya. Data collected by 30 questionnaires. Structural Equation Model (SEM) – PLS (Partial Least Square) has been employed to analyze the data. The results showed that 3 (three) hypotheses are accepted and 9 (nine) hypotheses are rejected. Five independent variables (employee development, employee communication, rewards and recognition, and leadership) had no significant effect on OCB with employee engagement as an intervening variable.